Rop thammai læ rop ph̄ưa khrai? - Suphot Dāntrakūn (Sathāban Witthayāsāt sangkhom, 2002)
On the political situation in southeast Asia with reference to conflicts existing in Vietnam, Kampuchea, Laos, and Thailand.